Phenotypic variation and correlation of traits in Philippine hybrid rice varieties: Phenotypic analysis of hybrid rice traits (Journal of the Bangladesh Agricultural University, 2019)
Understanding the phenotypic variation and correlation in hybrid rice varieties will lead to proper utilization of these genetic resources. Grain yield (GY), the primary trait, and its secondary traits such as days to 50% flowering (DF), days to maturity (DM), grain length (GL), grain weight (GW), number of filled grains panicle-1 (NFGP), one thousand grain weight (OTGW) panicle length (PL), panicle weight (PW), spikelet fertility (SF), and spikelet number panicle-1 (SNP) of 13 hybrid rice in two environments (E1 and E2) were analyzed using combined analysis of variance (ANOVA) and correlation analysis. High significant variation was found among hybrids (G) in all traits except for GW while there was at least significant result among environments (E) in DF, DM, GL, GW, PW, and OTGW, and in GxE in DF, DM, GW, NFGP, PW, and SNP. Therefore, E1 hybrids were early flowering and maturing, had longer, wider, and more grains, had longer panicles, and higher yield while in E2 hybrids were late flowering and maturing, and had heavier grains. However, among the 13 hybrid rice, M1 had the highest GY and GL in each environment with a mean of 9.57 t ha–1 and 9.75 mm, respectively. M1, therefore, can be recommended to farmers for varietal utilization. Correlation analysis, on the other hand, found 15 and 17 significant correlations in E1 and E2, respectively. Of the correlation results, it was found out that among the secondary traits, only NFGP was consistently, significantly and positively correlated with GY in two environments. The result implied that attaining higher yield in hybrid rice cultivation can be possible by giving more attention to the plants during the grain filling stage.J. Bangladesh Agril. Univ. 17(2): 179–186, June 2019